Aplikasi Pembelajaran Berbasis Android (E-Learning) Di Ma.Daruttaqwa Gresik - Heri Susanto; Tjatursari Widiartin; Firman Hadi Sukma Pratama (Melek IT : Information Technology Journal, 2016)
Android Application Based Learning (E-learning) For High School of Madrasah Aliyah especially Daruttaqwa. There are two urgent matters of the background for the manufacture of e-learning applications, namely: First, weakness learning pattern (face to face learning in the classroom) that is used by MA.Daruttaqwa. Second, the current technological developments that have advanced rapidly in education can improve the condition or thelearning process. The main objective contained in this thesis is making application to Android Based Learning (E-learning) in MA.Daruttaqwa Gresik.Development of information systems in the making software using the Waterfall method. Data collection methods used in this study is the observation and interview or an interview with the topics that will be taken. The method of analysis used in the design and construction Application Based Learning Android (E-learning) is a method of designing an object-oriented through the stages of manufacture of UML that includes Use Case, Class diagrams, Sequence diagrams and Activity diagrams, Deployment diagrams drafting data bases and drafting screen using tools android studio.While the result is the availability ofsupportsystem of teaching and learning activities that can be accessed online.Application ofLearning (E-learning) facilities-based Android adds teachers and students in terms of communicating, providing course material, assignments ofsubjects online. With the Android App Based Learning (E-learning) can help the learning process more optimal. Make it easy for teachers to be able to distribute learning materials for pupils in MA.Daruttaqwa and students can easily get the subject matter. Android e-learning can be used as additional discussion ofthe media to discuss the subject matter is not yet complete and can take on tasks given by the teacher